Pembinaan Penggunaan Aplikasi Permodelan dan Simulasi Pada UMKM Handcarft Untuk Meningkatkan Produktifitas - Citra Indah Asmarawati; Elva Susanti; Tukino Tukino; Bahariandi Aji Prasetyo; Elsya Tarigan Paskaria Loyda Tarigan; Anggia Arista (LPPM Universitas Putera Batam, 2023)
Batam City has a strategic geographical location close to several developed and developing countries. In the current era of information technology, it is hoped that business actors, especially micro, small and medium enterprises (MSMEs) can utilize digital media to market both new and old products to ensure business continuity. The sustainability of SMEs is important because the SME sector is the largest producer of GDP and employment. The simulation approach begins with the creation of a realistic system model. A model must be able to show how the various components in a system interact to truly describe the behavior of the system. After the model is created, it is converted into a computer program so that it can be simulated. During the mentoring period, the service team continued to monitor and evaluate the development of Handcraft MSMEs. They provide useful feedback and suggestions to improve the use of modeling and simulation applications and the productivity of MSMEs. Apart from that, the service team also helps in overcoming technical obstacles or problems that may arise during application implementation. The results of the evaluation are used as a basis for compiling recommendations and guidelines for the use of modeling and simulation applications in MSME Handcraft more broadly.